Why People in Prison Disobey the Rules: The Influence of Legitimacy on Misconduct in South Korean Prisons - Yim, Ha-Neul (Victims & offenders, 2024)
Research has demonstrated that individuals with higher levels of perceived legitimacy toward police or legal institutions are less likely to engage in antisocial behavior. However, a limited number of empirical studies have directly examined the relationship between the perceived legitimacy of prison officers and misconduct in prisons. The goal of this study is to examine the role of legitimacy in misconduct among people incarcerated in South Korean prisons. Using a nationwide sample of adults in correctional facilities in South Korea, logistic regression models are used to examine whether the perceived legitimacy of prison officers is associated with verbal and physical aggression against officers and other incarcerated persons. The equality of regression coefficients test is employed to examine whether the independent variable has varying impacts on each measure of interpersonal aggression. The study found that perceived legitimacy was negatively related and varied with the target of misconduct, with a larger influence on interpersonal aggression toward prison officers than those toward other incarcerated individuals. The findings are consistent with the normative perspective and suggest the need for policies encouraging just and fair management of prison populations by prison officers to sustain order in prisons. Policy implications are discussed.